Penggunaan Apliksi Geogebra dan Minat Belajar Matematika pada Siswa SMKN 34 Jakarta - Sakti, Essy Malays Sari; Marnis, Marnis; Herwanto, Agus (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Community Service is one of the obligations of lecturers that can be carried out outside the campus. Community service activities have been carried out at SMK 34 Jakarta with the aim of enlightening students on the use of the Geogebra Application. The research was conducted to determine the effect of using the Geogebra application on students’ interest in learning mathematics at SMKN 34 Jakarta, class XI with a total of 8 classes with 4 study programs, while the research data was taken randomly with a total of 20 students. The approach in this research uses descriptive quantitative with linear regression as data analysis, and software to assist calculations using the Ms. application. Excel. Before being analyzed in a questionnaire with 15 questions, X and Y data were checked using the Pearson bivariate validity test. and shows a valid value with a calculated r value greater than the r table value and for the Cronbach alpha reliability test shows a calculated value of more than 0.77. The results of the analysis show a significance value greater than 0.05 which states that there is no significant relationship between the use of the Geogbra application and students’ interest in learning at SMA 34 Jakarta.